Voices from the field: exploring service providers' insights into service delivery and AAC use in Canada. - Lackey, Stephanie; Burnham, Seamus; Watson Hyatt, Glenda; Shepherd, Tracy; Pinder, Shane; Davies, T. Claire; Batorowicz, Beata (AAC: Augmentative & Alternative Communication, 2024)
Use of augmentative and alternative communication (AAC) often relies on the involvement of AAC service providers; however little is known about how AAC services are delivered across Canada. This study aimed to explore AAC service provision and factors influencing use of AAC from the perspectives of service providers across Canada who are involved in providing and/or supporting use of AAC systems. The 22 participants from nine (of the 10) provinces participated in online focus groups. Participants were speech-language pathologists, occupational therapists, communicative disorders assistants, and a teacher. Transcripts of the audio recordings were analyzed using reflexive thematic analysis. Four themes were generated that reflect service-related factors contributing to the use of AAC in Canada: Support of Organizational Structures, Concordant Relationships and Goals, Making the Right Decisions, and Influence of Knowledge and Attitudes. These themes highlight how government systems, key stakeholders, assessment practices, and knowledge of AAC influence service provision and use of AAC. Voices from across Canada highlighted shared experiences of services providers as well as revealed variability in service delivery processes. The findings bring to attention a need for further research and development of service provision guidelines to support consistency, quality in practice, and equity in AAC services.